Germline RET variants underlie a subset of paediatric osteosarcoma. Issue 1 (16th March 2020) - Kovac, Michal; Woolley, Connor; Ribi, Sebastian; Blattmann, Claudia; Roth, Eva; Morini, Marco; Kovacova, Monika; Ameline, Baptiste; Kulozik, Andreas; Bielack, Stefan; Hartmann, Wolfgang; Ballinger, Mandy L; et al.
Abstract : Background: Although considerable effort has been put into decoding of the osteosarcoma genome, very little is known about germline mutations that underlie this primary malignant tumour of bone. Methods and results: We followed here a coincidental finding in a multiple endocrine neoplasia family in which a 32-year-old patient carrying a germline pathogenic RET mutation developed an osteosarcoma 2 years after the resection of a medullary thyroid carcinoma. Sequencing analysis of additional 336 patients with osteosarcoma led to the identification of germline activating mutations in the RET proto-oncogene in three cases and somatic amplifications of the gene locus in five matched tumours (4%, n=5/124 tumours). Functional analysis of the pathogenic variants together with an integrative analysis of osteosarcoma genomes confirmed that the mutant RET proteins couple functional kinase activity to dysfunctional ligand binding. RET mutations further co-operated with alterations in TP53 and RB1, suggesting that osteosarcoma pathogenesis bears reminiscence to the stepwise model of medullary thyroid carcinoma. Conclusions: After Li-Fraumeni-predisposing mutations in TP53, RET becomes the second most mutated cancer-predisposing gene in the germline of patients with osteosarcoma. Hence, early identification of RET mutation carriers can help to identify at-risk family members and carry out preventive measures.